(untitled) (Journal of Naval Architecture and Marine Engineering, 2011)
This work is focused on the numerical solution of unsteady double-diffusive free convective flow along a vertical isothermal cylinder in the presence of a transverse magnetic field, first-order homogeneous chemical reaction, thermal radiation and Soret and Dufour effects. The Rosseland approximation is used to describe the radiative heat flux in the energy equation. The governing equations are formulated and a numerical solution is obtained by using an explicit finite-difference scheme. The solutions at each time step have been found to reach the steady state solution properly. Representative results for the fluid velocity, temperature and solute concentration profiles as well as the local heat and mass transfer rates for various values of the physical parameters are displayed in both graphical and tabular forms. DOI: http://dx.doi.org/10.3329/jname.v8i1.7250